2021
DOI: 10.3390/antiox10111800
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Added-Value Compounds from Orange and Spinach Processing Residues: Green Extraction of Phenolic Compounds and Evaluation of Antioxidant Activity

Abstract: Phenolic compounds recovery by mechanical stirring extraction (MSE) was studied from orange and spinach wastes using water as a solvent. The statistical analysis showed that the highest total polyphenol content (TPC) yield was obtained using 15 min, 70 °C, 1:100 (w/v) solid/solvent ratio and pH 4 for orange; and 5 min, 50 °C, 1:50 (w/v) solid/solvent ratio and pH 6 for spinach. Under these conditions, the TPC was 1 mg gallic acid equivalent (GAE) g−1 fresh weight (fw) and 0.8 mg GAE g−1 fw for orange and spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Several techniques have been used to recover polyphenols from olive oil and wine by-products. Conventional extraction with solvents, also called solid-liquid extraction (SLE) or maceration, is the most applied technique from an industrial point of view, to extract bioactive compounds from matrices of vegetable origin [7,81]. Many solvents have been studied for polyphenols extraction, but the preferred systems for food, pharmaceutical, or cosmetic applications are those based on water and ethanol [82].…”
Section: Extraction Processesmentioning
confidence: 99%
“…Several techniques have been used to recover polyphenols from olive oil and wine by-products. Conventional extraction with solvents, also called solid-liquid extraction (SLE) or maceration, is the most applied technique from an industrial point of view, to extract bioactive compounds from matrices of vegetable origin [7,81]. Many solvents have been studied for polyphenols extraction, but the preferred systems for food, pharmaceutical, or cosmetic applications are those based on water and ethanol [82].…”
Section: Extraction Processesmentioning
confidence: 99%
“…Higher antioxidant activity of ethanolic extracts than that of methanolic extracts corresponded with the higher TPC in ethanolic extracts. This relation between TPC and antioxidant activity may result from the absence of any potential interfering (absorbing) species which do not have antioxidant activity 53 . However, this relation is dependent on type of substrate and target compounds.…”
Section: Resultsmentioning
confidence: 99%
“…In all extracts, the ABTS assay indicated significantly higher antioxidant activity than the DPPH assay, which was followed by the FRAP assay. The predominance of antioxidant activity shown by the ABTS and DPPH over that shown by the FRAP may be due to the predominance of phenolic compounds that are efficient at scavenging radicals and smaller quantity of non-phenolic compounds that may be able to reduce FRAP, account for the reducing power but are not so efficient at scavenging radicals 53 . Similarly, Yu et al 46 reported that the ABTS assay indicated that the activity of wheat bread extract was 10–20-times higher than what the DPPH assay indicated.…”
Section: Resultsmentioning
confidence: 99%
“…Citrus waste is a high source of polyphenolic compounds because the peel of citrus fruits contains a larger amount of polyphenols, compared to the edible portion of the fruit [ 41 ]. Montenegro-Landívar et al [ 37 ] proved that the orange and spinach residues are rich in polyphenols (0.51 ± 0.02 mg GAE/g fw and 0.47 ± 0.03 mg GAE/g fw, respectively) and have high antioxidant activity (2.27 mg TE g-1 and 0.04 mg TE g-1, respectively) in comparison with carrot, celery, kiwi, strawberry, and broccoli and lower antioxidant activity than kale and white and red grape. Suleria et al [ 61 ] found that fruit peels have a diverse range of phytochemicals: the mango peel exhibited the highest phenolic content for TPC (27.51 ± 0.63 mg GAE/g) and TFC (1.75 ± 0.08 mg QE/g), while the TTC (9.01 ± 0.20 mg CE/g) was slightly higher in the avocado peel than in the mango peel (8.99 ± 0.13 mg CE/g).…”
Section: Fruit and Vegetable Peels As A Rich Source Of Polyphenols An...mentioning
confidence: 99%
“…OnionProtocatechuic acid, quercetin 3,4′-diglucoside, quercetin-3-glucoside, quercetin, kaempferol Celano et al[34] Allium sativum Garlic Caffeic acid, p-coumaric, ferulic, and di-ferulic acids Kallel et al[35] Solanum tuberosum Potato Caffeic acid, chlorogenic acid, ferulic acid, gallic acid, protocatechuic acid Singh et al[36] Spinacia oleracea Spinach Caffeic acid, ferulic acid, rutin Montenegro-Landívar et al[37] Solanum lycopersicumTomatoCaffeic acid, procatchoic acid, vanillic acid, catechin, gallic acid Elbadrawy and Sello[38] …”
mentioning
confidence: 99%